Analysis of the Influence of Knowledge, Service Quality, and Digital Banking on Students' Interest in Becoming Customers of Islamic Banks in Semarang City - Vara Soraya Auliya Kasih; Aris Sunindyo Arif Mursito; R Gunawan Setianegara (Politeknik Negeri Semarang, 2025)
This study aims to analyze and obtain empirical evidence regarding theinfluence of knowledge, service quality, and digital banking on students'interest in becoming customers of Islamic banks in Semarang City, bothsimultaneously and partially. The population of this study includes allstudents in Semarang. The sampling technique used is purposivesampling with a total of 100 respondents. Primary data was obtainedthrough the distribution of questionnaires. The data analysis modelapplied was Multiple Linear Regression Analysis. Data analysistechniques included the F-test, the coefficient of determination (R²), andthe t-test. The analysis results show that knowledge, service quality, anddigital banking variables simultaneously have a significant influence onstudents' interest in becoming customers of Islamic banks in Semarang.